2018
DOI: 10.1177/2309499018768032
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of four parameters to assess acetabular dysplasia and acetabular dysplasia rates in primary hip osteoarthritis patients: A study in Turkish population

Abstract: We identified a high rate of AD in primary coxarthrosis patients undergoing total hip arthroplasty in the study population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…The measurement of the femoral head coverage ratio is shown in Fig. 3 [13]. The measurement of the acetabular width, depth, and depth to width ratio are shown in Fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The measurement of the femoral head coverage ratio is shown in Fig. 3 [13]. The measurement of the acetabular width, depth, and depth to width ratio are shown in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Patient factors (history of neurological disease and weakness of abduction muscles), morphological factors (center-edge angle, femoral neck offset, and leg length discrepancy), and surgical factors (surgery approach, choice of prosthesis, and repair of the short external rotator tendons) were reported to play an important role in dislocation after bipolar hemiarthroplasty [912]. Adanir et al reported measurements such as the center-edge angle and acetabular depth (which evaluated the shallowness of the acetabulum) were used to assess acetabular dysplasia [13], but the relationship between these measurements and dislocation after bipolar hemiarthroplasty for patients without acetabular dysplasia remained unclear. In the current study, we explored the morphological risk factors for dislocation after bipolar hemiarthroplasty.…”
Section: Introductionmentioning
confidence: 99%
“…This causes a high rate of adults suffering from early coxarthrosis (4). For example, in a Turkish population of more than 200 patients over 80% of cases of hip osteoarthritis were linked to hip dysplasia (5). In adults hip dysplasia is usually classified by Hartofilakidis(6) depending on the grade of dislocation of the femoral head.…”
Section: Introductionmentioning
confidence: 99%
“…Developmental dysplasia of the hip (DDH) is a disease characterized by hip dislocation or subluxation and acetabular morphological abnormalities observed in infants and children 5 . The incidence of DDH is racially different and is reportedly high in Japanese 6 , Singaporean 5 , Native American 7 , and Turkish populations 8 , and in Sami populations in Scandinavia 9 . In the Japanese population prior to 1965, dislocation was present in approximately 1.1% to 3.5% of all newborns 6 , and severe subluxation was present among adults 10 (Fig.…”
mentioning
confidence: 99%